Ketidakmampuan Siswa dalam Mengatasi Permasalahan Konseptual Setelah Menyelesaikan Soal Simulasi Asesmen Momentum dan Impuls - Diah Ambarwulan (MJI Publisher by PT Mitra Jurnal Indonesia, 2023)
Abstract Should work on formative assessments and summative assessment simulations can provide an overview of solving conceptual problems for students. So this study has the aim of finding a relationship between problem-solving done in students' physics textbooks with students' conceptual understanding. The number of questions that students completed on momentum and impulse material is estimated to be around 50 to 100 questions with an average of about 75 questions. Based on the teaching experience found in six classes (grade 10 of senior high school), students do not experience much difficulty in using physics formulas. However, it was found that they still had conceptual problems and there was a relationship between the number of questions worked and conceptual understanding. Because momentum and impulse are vector quantities, students have problems mastering vectors (direction). so that after being explored it turns out that students have conceptual problems in solving problems involving the direction of object movement, especially for objects that experience two conditions before and after the collision. So it is concluded that solving problems using traditional textbooks has a limited effect on conceptual understanding. Abstrak Sebaiknya pengerjaan asesmen formatif dan simulasi asesmen sumatif dapat memberikan gambaran pemecahan masalah konseptual bagi siswa. Maka penelitian ini bertujuan untuk menemukan hubungan antara pemecahan masalah yang dikerjakan dari buku teks fisika siswa dengan pemahaman konsep siswa. Jumlah soal yang diselesaikan siswa pada materi momentum dan impuls diperkirakan sekitar 50 hingga 100 soal dengan rata-rata sekitar 75 soal. Berdasarkan pengalaman mengajar di enam kelas (kelas 10 SMA), siswa tidak mengalami banyak kesulitan dalam menggunakan rumus fisika. Namun, ditemukan bahwa mereka masih memiliki masalah konseptual dan ada hubungan antara jumlah soal yang dikerjakan dengan pemahaman konsep siswa. Karena momentum dan impuls merupakan besaran vektor, umumnya siswa kesulitan menguasai permasahan yang berhubungan dengan vektor (arah). Sehingga setelah dieksplorasi ternyata siswa memiliki masalah konseptual dalam menyelesaikan masalah yang menyangkut arah gerak benda, khususnya untuk benda yang mengalami dua kondisi sebelum dan sesudah tumbukan. Jadi disimpulkan bahwa pemecahan masalah dengan menggunakan buku teks tradisional memiliki efek terbatas pada pemahaman konseptual.